EFFECT OF RAW MATERIALS VARIATIONS AND FERMENTATION TIME ON THE SENSORY CHARACTERISTICS OF TERASI - Medal Lintas Perceka; Mahaldika Cesrany; Anis Khairunnisa; I Gusti Ayu Budiadnyani; Pinky Natalia Samanta (Universitas Mataram, 2025)
Terasi is a traditional fermented product from Indonesian. Terasi was favoured by Indonesian people and used as spice in various dishes. The purposed of this study was to evaluate the effect of raw materials variations and fermentation time on the sensory hedonic of terasi. There were four varitions, terasi made from rebon, vaname shrimp, lemuru fish meat and lemuru fish head and bones. Each terasi was fermented for 4,5 and 6 weeks. Data anlysed used ANNOVA followed by Duncan’s further test for result that showed significant differences. The result showed that variations in raw materials showed a significantly different effect (P<0,05) on the sensory-hedonic (appearance, smell, taste, and tecture) of terasi, while variations in fermentation time didn’t show a significantly different (p>0,05). In general, terasi that was most preferred by panelists was terasi made from rebon which was fermented for 4 weeks with the specifications of clean appearance, specific to very specific terasi types, which has a distinctive shrimp-like smell and flavour. It also has dry and crumble texture.